Market Reaction to the Russian Invasion of Ukraine in the Oil and Gas Industry on the Indonesian Stock Exchange - Mokodaser, Rexaldo C.; Mangantar, Maryam; Rumokoy, Lawren J. (Formosa Journal of Applied Sciences, 2024)
The economy in Indonesia experiences growth every year. The capital market is the most important part for economic progress in Indonesia. The aim of this research is to determine the information content of market reactions to the Russian invasion of Ukraine in Indonesia, as well as differences in abnormal returns and trading volume activity before and after the Russian invasion. This type of research is quantitative research using secondary data. The sample used was 9 companies in the Oil and Gas industry using the purposive sampling method. Then test the differences using the paired sample t-test. The results of this study show that there are no significant differences in abnormal returns and there are differences in trading volume activity before and after the Russian invasion of Ukraine in Indonesia.